Structural and Modal Analysis of a Small Wind Turbine Blade Considering Composite Material and the IEC 61400-2 Standard - Miriam Vázquez; Victor López; Rafael Campos; Erasmo Cadenas; Paulina Marin (Energies)
IEC 61400-2 establishes the Simplified Load Method for designing low-power wind turbine blades without considering dynamic loads in the simplified load methodology. This paper analyzes the load hypotheses established by the standard, also considering the natural frequencies in a 900 W blade. The research methodology begins with the design parameters, the application of the BEM Method, and the use of the QBlade software. Then, the load hypotheses of the standard are defined. Finally, the structural design and the modal and structural analysis of the blade were conducted using FEM-based software. The results show that the minimum participation factors are found on the z-axis and the maximum on the x- and y-axis, and their magnitudes decrease when the natural frequency increases. In general, the principal maximum stresses are located in the middle section of the blade, in the external fiberglass layer, both on the intrados and extrados sides. In conclusion, structural scenarios were established to relate the participation factors of the modal analyses with the load hypotheses. The critical scenarios are at natural frequencies below 280 Hz.